Business models of vertical integration in the beauty industry in the United States: analysis of economic efficiency - Poltavets, Karyna (Global Prosperity, 2025)
Abstract. The beauty industry in the United States is the global leader in aesthetic and cosmetic services. Traditionally, vertical integration of businesses in various segments of the beauty market has been little studied in terms of the advantages and disadvantages of business consolidation. After the coronavirus pandemic, major American operators in the beauty industry faced a number of operational problems that led to a decline in the operational profitability of their businesses. In these conditions, vertical consolidation became one of the ways to solve the existing problems of inefficient operations. The purpose of the article was to highlight the features of the vertical integration business model in the US beauty industry and to assess its economic effects. Vertical integration business models are not widespread in the US beauty industry, as this market has traditionally been dominated by business models in which the parent company enters into agreements with franchisees to standardize business processes and receive remuneration. However, the example of vertical integration of Regis Corporation and its franchisees demonstrates the economic effects of consolidating activities. The complete acquisition of the franchisee salon network by Regis Corporation in 2024 made it possible to maintain operating profitability and increase business profitability. The growth in operating income and reduction in costs following the acquisition of 314 franchisee salons was a strategic solution to the operational problems that existed at Regis Corporation due to the significant dominance of franchisee-operated salons. Vertical consolidation, as exemplified by Regis Corporation, indicates that strategic decisions to integrate the operations of the parent company and franchisees can promote short-term operational efficiency. However, the long-term effects of vertical integration and the new business model remain uncertain. The main advantages of the vertical integration business model in the beauty industry include: elimination of intermediary activities, optimization of business operations, full control over sales channels and direct access to the customer base of the combined beauty salons, and the consolidation of brands into a single network of beauty salons.